LITERATURE REVIEW: JENIS PENYAKIT AKIBAT KERJA, PENYEBABNYA DAN MEKANISME PENYEBARAN DALAM INDUSTRI - Muhammad Zukhrufuz Zaman; Achmad Syarifuddin; Abdul Hakim Zakkiy Fasya; Agus Aan Adriansyah (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2022)
Every process of activity in the industry must pay attention to the K3 factors in order to obtain comfortable, safe and safe working conditions. PAK is an important concern at this time, considering that PAK appears after the activity takes place, so workers often ignore the risks that arise that can cause PAK. This study aims to review the types of PAK, their causes and the mechanism of spread in industry. This research is a literature review study. The data source comes from google scholar and garuda portal from 2016-2021. Keywords used Occupational Diseases in industry. The overall results of the articles through screening amounted to 20 articles as a reference to find out the type of PAK, its causes and the mechanism of spread in the industry. The results showed that most PAK in workers is a disorder of the respiratory system and skin diseases (dermatitis). Diseases of respiratory system disorders such as ARI disease, pulmonary diseases. The complaints that workers feel are (cough, runny nose, shortness of breath and wheezing sounds). Meanwhile, skin diseases exposed to workers mostly feel itching, redness, thinning of the epidermal layer and dry skin. The conclusion of this literature review explains that the types of PAK that are often found in industrial workers are respiratory system disorders and skin diseases, the causes of PAK are dominated by dust, substances and chemicals in the work environment. The mechanisms of substances and chemicals entering the body are mostly exposed through the respiratory tract and skin. Workers are advised to continue to prioritize the K3 factor to minimize the occurrence of PAK and be aware of the causes of PAK. Workers are also urged to be aware of substances and materials that have a harmful impact on the health of workers by using PPE while working and complying with SOPs in the industry.